An overview of portuguese wordnets - Paiva, Valeria de (2016)
Semantic relations between words are key to building systems that aim to understand and manipulate language. For En- glish, the “de facto” standard for representing this kind of knowledge is Princeton’s WordNet. Here, we describe the wordnet-like resources currently available for Portuguese: their origins, methods of creation, sizes, and usage restrictions. We start tackling the problem of comparing them, but only in quantitative terms. Finally, we sketch ideas for potential collaboration between some of the projects.